2020
DOI: 10.3389/fpsyg.2020.582894
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Empowerment: Predictors and Benefits of Shared Leadership in Organizations

Abstract: Leadership plays an essential part in creating competitive advantage and well-being among employees. One way in which formal leaders can deal with the variety of responsibilities that comes with their role is to share their responsibilities with team members (i.e., shared leadership). Although there is abundant literature on how high-quality peer leadership benefits team effectiveness (TE) and well-being, there is only limited evidence about the underpinning mechanisms of these relationships and how the formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…The opposite seemed to be true, as the perceived identity leadership of the formal leader increased to a greater extent in the walking groups who received the 5R S program, compared to those in the comparison condition. These findings are in line with earlier work in the organisational context [ 47 ] and in the sport context [ 48 ], showing that teams with higher, compared to lower, peer leadership quality perceived their formal leader to be a better leader. These results might constitute an important motivator to encourage formal leaders of walking groups to harness and empower the leadership talents within their group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The opposite seemed to be true, as the perceived identity leadership of the formal leader increased to a greater extent in the walking groups who received the 5R S program, compared to those in the comparison condition. These findings are in line with earlier work in the organisational context [ 47 ] and in the sport context [ 48 ], showing that teams with higher, compared to lower, peer leadership quality perceived their formal leader to be a better leader. These results might constitute an important motivator to encourage formal leaders of walking groups to harness and empower the leadership talents within their group.…”
Section: Discussionsupporting
confidence: 91%
“…Our second aim was to ensure that, although 5R S focused on strengthening the quality of peer leadership, this would not be at the expense of the leadership qualities of the formal leader. In this vein, earlier research in organisation and sport contexts [ 47 , 48 ] demonstrated that the opposite is true — teams with higher-quality peer leaders perceived their managers and coaches to be better leaders. We thus expect that in this context too, the increase in identity leadership qualities of the formal leaders in the 5R S condition would be greater than those of the formal leaders in the comparison condition (H2).…”
Section: Introductionmentioning
confidence: 99%
“…Facing the rapidly changing environment and the increase of complex tasks, the organization needs to have greater flexibility to deal with a series of non-routine, non-repetitive, complex and challenging team tasks. A single person is unlikely to be able to Edelmann et al (2020) . Therefore, digital leaders need authorization, and encourage employees to participate in the decision-making process.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…High-quality digital leaders succeed in creating a shared sense of “us” in the organization, and this organizational identification in turn produces positive results and helps reduce work stress. All in all, digital leaders will stimulate employee job crafting through promoting the usage of new digital technology, providing the direction for the organization, making “real-time” decisions and helping employee adjust ( Edelmann et al, 2020 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…However, physician training is largely focused on the individual, with an emphasis on clinical care of patients. Developing leadership skills in physician supervisors, organisations can make a large impact in the well-being of their clinicians and foster better patient care 18 25 28 29. Additionally, by understanding and targeting leadership, organisations can impact a large number of healthcare professionals and teams under each leader’s supervision.…”
Section: Introductionmentioning
confidence: 99%